Prevalence and Associations of Avascular Necrosis of the Hip in a Large Well-characterized Cohort of Patients With Inflammatory Bowel Disease. Issue 1 (January 2019) - Rolston, Vineet S.; Patel, Anish V.; Learch, Thomas J.; Li, Dalin; Karayev, Dmitry; Williams, Chadwick; Siddanthi, Madhavi L.; Targan, Stephan R.; Weisman, Michael H.; McGovern, Dermot P.B.
Abstract : Objectives: Avascular necrosis (AVN) is associated with significant morbidity potentially causing severe pain and disability; patients with inflammatory bowel disease (IBD) have a higher prevalence of AVN compared with non-IBD populations. The purpose of our study was to determine the prevalence of AVN in our IBD population and to evaluate these subjects for the presence of clinical characteristics associated with AVN on computed tomography (CT) imaging. Methods: In 1313 IBD patients with abdomen/pelvis CT scans, we identified 27 patients (2.1%) with CT findings consistent with AVN. Through historical chart review, we confirmed that most patients had prior exposure to steroids, although 2 patients had no documented steroid exposure at all. Results: We found that 59% of the concurrent radiology reports did not comment on the presence of AVN, suggesting that incidental CT findings of AVN among IBD patients are likely underreported. Notably, we found that 63% of these cases had documented complaints of low-back and/or hip pain. Using logistic regression, we found an association between anti–neutrophil cytoplasmic antibody–positive status across IBD ( p = 0.007) and a smoking history in Crohn disease ( p = 0.03) with the presence of AVN. Conclusions: We found that a significant proportion of IBD patients with AVN are reported in their records as having hip or low-back pain, and review of CT imaging under dedicated bone windows may identify AVN among this population. Our findings also suggest that additional etiological factors, beyond corticosteroids, contribute to the development of AVN in IBD. Further investigation is warranted regarding the mechanisms associated with AVN in IBD.